2017
DOI: 10.1155/2017/8370584
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination and Pharmacokinetic Study of Quercetin, Luteolin, and Apigenin in Rat Plasma after Oral Administration of Matricaria chamomilla L. Extract by HPLC‐UV

Abstract: A simple and sensitive HPLC-UV method has been developed for the simultaneous determination of quercetin, luteolin, and apigenin in rat plasma after oral administration of Matricaria chamomilla L. extract. The flow rate was set at 1.0 ml/min and the detection wavelength was kept at 350 nm. The calibration curves were linear in the range of 0.11–11.36 μg/ml for quercetin, 0.11–11.20 μg/ml for luteolin, and 0.11–10.60 μg/ml for apigenin, respectively. The intraday and interday precisions (RSD) were less than 8.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
3
16
1
Order By: Relevance
“…administration were observed after oral treatment. A double peak was observed in the drug concentration-time curve of LUT after oral administration, which is in accordance with that reported previously [20,24]. Enterohepatic circulation may account for this phenomenon because the doublepeak was not observed in the i.p.…”
Section: Pharmacokinetic Studysupporting
confidence: 92%
See 1 more Smart Citation
“…administration were observed after oral treatment. A double peak was observed in the drug concentration-time curve of LUT after oral administration, which is in accordance with that reported previously [20,24]. Enterohepatic circulation may account for this phenomenon because the doublepeak was not observed in the i.p.…”
Section: Pharmacokinetic Studysupporting
confidence: 92%
“…Several chromatographic assays have been established for determination of the concentrations of LUT, 7-O-gluA-LUT, DIO or CHR in plasma using HPLC, HPLC-MS/MS, or GC-MS [17][18][19][20][21][22][23][24][25][26]. However, the analytical method for simultaneous quantification of LUT, 7-O-gluA-LUT, DIO, and CHR in plasma has not been reported until now, which is a formidable task, especially the chromatographic separation of two isomers (DIO and CHR).…”
Section: Introductionmentioning
confidence: 99%
“…route, the oral administration of ProFine resulted in a bioavailability of 1.30%, 0.91%, and 2.89% for luteolin, quercetin, and kaempferol, respectively. These results are in agreement with the reported bioavailability data of the three flavonoids after oral administration in rodent models [26] , [27] , [28] , suggesting that co-administration of the three ingredients did not significantly alter their in vivo absorption and stability in the circulation.…”
Section: Resultssupporting
confidence: 92%
“…However, importantly, polyphenols have also been shown to inhibit the response to chemotherapeutic agents in leukemia cell lines and other cancers [ 39 – 43 ]. It is noteworthy that quercetin and apigenin are readily detectable in serum following dietary intake in both humans [ 44 ], and rat studies [ 45 ]. Furthermore, pharmacokinetic studies have shown that dietary intake of polyphenols, including quercetin, resulted in a plasma concentration of 2.3 μg/ml [ 44 ].…”
Section: Discussionmentioning
confidence: 99%